STRATEGI KOMUNIKASI HUMAS BNN DALAM MEMBERIKAN INFORMASI KEPADA PUBLIK - Didi Permadi; Akhmad Habibullah (Jurnal Pustaka Komunikasi, 2022)
This study focuses on Indonesian National Narcotics Agency (BNN) Public Relations in using communication strategies related to delivering information to the public in handling cases involving State Officials. This research was conducted to identify and describe the communication strategy and communication limitations carried out by BNN public relations regarding handling cases involving State Officials. This research uses a qualitative approach with a case study methodology through in-depth interviews as the primary data collection method. This study uses a constructivist paradigm in viewing the problem. The theory used in this study is the Berlo model of communication and communication strategy theory (SMCR). The results of this study indicate that BNN Public Relations does not use a particular communication strategy in conveying information to the public regarding the handling of cases involving State Officials. BNN Public Relations also does not have communication limitations regarding delivering information to the public.